Fuzzy spanners - Farshi, Mohammad (Journal of Advanced Computer Science & Technology, 2014)
Graphs have wide applications in variety of applications, especially network analysis. Spanners give a sparse approximation of any graph as well as complete graph, which has wide applications so far. Because of its applications, graph definitions generalized to fuzzy sets and fuzzy weighted graph defined and studied vastly in past and has applications in several fields. In this paper, we define spanners for fuzzy weighted graphs and well as points come from a fuzzy metric space. We propose some algorithm to compute such a spanner. Finally, we pose some open problem that can be considered for future works.